Productivity and efficiency of smallholder teff farmers in Ethiopia - Bachewe, Fantu Nisrane; Koru, Bethlehem; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2015)
A large proportion of Ethiopians derive their livelihood from smallholder agriculture. This has provided the impetus for the smallholder agriculture focused policies that have guided agricultural development efforts in Ethiopia over the past two decades. This work studies smallholder teff producers. Teff is an important crop in terms of cultivated area, share of food expenditure, and contribution to gross domestic product. Despite the remarkable growth in teff production in the last decade, the drivers of this growth are not well understood. In particular, there is a lack of evidence on the contribution of improvements in productivity to this growth and the link between farm size and productivity. More-over, doubts exist on whether it is possible to sustain such growth on landholdings that are declining in size. This study employs data envelopment analysis on a recently collected large-scale farm household survey dataset to measure and explain the relative productivity and efficiency of smallholder teff producers.